2018
DOI: 10.1111/aji.12995
|View full text |Cite
|
Sign up to set email alerts
|

Interferon epsilon in the reproductive tract of healthy and genital herpes simplex virus‐infected pregnant women: Results of a pilot study

Abstract: Interferon epsilon increased across pregnancy, but was less abundant in women with HSV. This pilot investigation cannot make any definitive conclusions. However, animal models suggest that IFNe may protect against STIs. Thus, larger studies are required to validate expression of IFNe in the reproductive tract of pregnant women with and without genital infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 39 publications
1
14
0
1
Order By: Relevance
“…Herein, we used immunohistochemistry to show that IFNe expression in the myometrium and cervix was stronger in late gestation compared to mid-pregnancy, suggesting a gestational age-dependent increase that is consistent with a prior human study [ 8 ]. IFNE expression was observed to fluctuate based on the menstrual cycle in both non-pregnant mice and humans, which led to the proposed hormonal regulation of IFNe expression in the reproductive tract, particularly in the endometrium [ 2 , 5 ].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Herein, we used immunohistochemistry to show that IFNe expression in the myometrium and cervix was stronger in late gestation compared to mid-pregnancy, suggesting a gestational age-dependent increase that is consistent with a prior human study [ 8 ]. IFNE expression was observed to fluctuate based on the menstrual cycle in both non-pregnant mice and humans, which led to the proposed hormonal regulation of IFNe expression in the reproductive tract, particularly in the endometrium [ 2 , 5 ].…”
Section: Discussionsupporting
confidence: 76%
“…Of note, the protective effects of rmIFNe reported in the latter study were less potent than those of rmIFNb [ 51 ], suggesting that additional type I IFN responses beyond those provided by constitutive IFNe expression are necessary for maximum protection. Reduced or impaired expression of IFNe may also increase disease susceptibility in humans, as reduced vaginal IFNe was observed in HSV-infected pregnant women compared to healthy pregnant women [ 8 ]. A study in rhesus macaques showed that the expression of IFNe in the rectal mucosal tissue was not altered by simian immunodeficiency virus (SIV) infection [ 4 ], which is consistent with the results of the current study demonstrating that the presence of viruses such as HPV does not alter cervical expression of IFNe.…”
Section: Discussionmentioning
confidence: 99%
“…Mice: IFN-γ Humans: IFN-γ Mice: IFN-λ2, IFN-λ3 [128,129] Humans: IFN-λ1, IFN-λ2, IFN-λ3 IFN-λ4 (variably pseudogenic) [130,131] Member expression IFN-α/IFN-β: Plasmacytoid DCs Macrophages Fibroblasts Epithelial cells [7] Others: Female reproductive tract (IFN-ε) [77] Keratinocytes (IFN-κ) [132] NK cells T cells Type I innate lymphoid cells [11] Epithelial cells of intestine and lung [133,134] Plasmacytoid DCs [135] Downstream signaling complex ISGF3 complex (STAT1/STAT2/IRF9) [125] STAT1 homodimers [125] ISGF3 complex (STAT1/STAT2/IRF9) [16] Key activators IRF3, IRF5, IRF7, IRF8, various STAT TFs [2] AP-1, CREB/ATF, NFAT, T-bet, Eomes, various STAT TFs [2] IRF1, IRF3, IRF7, NF-κB. various STAT TFs [2] a Abbreviations: DCs, dendritic cells; TFs, transcription factors.…”
Section: Three 'Model' Mucosal Virusesmentioning
confidence: 99%
“…Patients deficient in IFNAR1 or related signaling molecules often present with HSV encephalitis [34,75,76]. Of interest, HSV-2 is restricted by IFN-εa recently described type I IFN that is constitutively expressed in a hormonally regulated manner within the female reproductive tract in humans and mice [77,78]. Mice lacking IFN-ε (Ifne -/-) exhibit decreased baseline expression of many ISGs in the reproductive tract, as well as increased replication of HSV-2 within the reproductive tract and increased spread of the virus into the spinal cord and brain stem, relative to wild-type animals [78].…”
Section: Antiviral Activities Of Ifnsmentioning
confidence: 99%
“…Para confirmar estos hallazgos en humanos, se tomaron muestras cérvico-vaginales de mujeres embarazadas y se midieron las concentraciones de IFN-ε, tanto en mujeres sanas como en mujeres con VHS. Se encontró un aumento de IFN-ε durante el embarazo, que fue mayor en las mujeres sanas en comparación con aquellas que tenían VHS 126 .…”
Section: Interferón éPsilonunclassified